Efficiency of different heterologous promoters in the unicellular microalga Chlamydomonas reinhardtii. (6th March 2013) - Díaz‐Santos, Encarnación; de la, Marta; Vila, Marta; Vigara, Javier; León, Rosa
<x xml:space="preserve">Abstract</x> Despite the biotechnological interest of microalgae, no robust and stable methods for genetic transformation of most microalgal strains exist. The scanty and disperse data about the efficiency of heterologous promoters in microalgae and the use of different transformation methods, DNA quantities and reporter genes in the existing studies makes very difficult a real comparison of their efficiency. Using Chlamydomonas reinhardtii as a host, we have evaluated the efficiency of the heterologous promoters of cauliflower mosaic virus 35S (CaMV 35S) and Agrobacterium nopaline synthase (NOS) genes. These promoters were fused to the paromomycin conferring‐resistance aminoglycoside 3′‐phosphotransferase encoding gene (APHVIII), and C. reinhardtii was transformed by the glass beads agitation method. The transformation efficiency and the APHVIII transcript and protein levels were evaluated in a series of transformants for each promoter. The chimeric promoter HSP70A/RBCS2 and the promoter‐less APHVIII marker gene were used for comparison. We found significantly higher transformation efficiencies and higher level of APHVIII expression in those transformants harboring the NOS promoter than in those transformed with CaMV 35S promoter. The NOS promoter, widely used for genetic manipulation of higher plants, has been very rarely used for the transformation of microalgae. The results shown here suggest the possibilities of this heterologous promoter as an efficient system for the genetic manipulation of microalgae. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29: 319–328, 2013